Design and Implementation of an Android based New Student Admissions Classification System using the Vikor Method - Wahyu Soataon Hasibuan; Heri Santoso (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
Today's technological developments make all aspects of life easier. One form of convenience that can be found in the world of lectures is a digital student graduation information system. In this study the authors designed an android-based new student admission classification system using the vikor method. In simple terms, the vikor method can be used to perform multicriteria ranking and weighting of each assessment criterion. In the implementation of the North Sumatra State Islamic University Independent Examination, there are several materials to be tested such as Religious Sciences, General Sciences, Arabic, English, and Interviews where the system still uses a passing grade where its application is considered less efficient. The use of the vikor method in this study is intended to carry out the process of ranking student grades based on predetermined weights based on the criteria of several materials tested. In this study, the creation of an android application using the app inventor platform. The results in this study indicate that the vikor method can be implemented in the new student admission classification system and perform ranking based on the exam results that have been carried out using an android smartphone.